Detection of QTLs associated to DBH in a Eucalyptus grandis x Eucalyptus Globulus monoprogeny - Torres-Dini, Diego Gabriel [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
In Uruguay, reforestation with Eucalyptus sp. is of fundamental importance to produce paper, pulp and wood. The productivity of these continually grows due to application of breeding techniques, such as hybridization. This study aimed to investigate genetic parameters, productivity, stability, adaptability and to identify SNP markers associated with the diameter breast height (DBH) for to select Eucalypts grandis x Eucalyptus globulus full-sibs hybrid clones. The study was conducted in a clonal test, repeated at two different soils, in the state of Rio Negro, Uruguay. The population was phenotypically characterized to the DBH at 48 months of age and cambium tissues of each individual were sampled for genotyping with EuCHIP60K chip. The mean growth in DBH was similar between both places. The genotype-environment interaction was the simple type, with high genotype correlation in clones’ performance between environments (0.708), indicating the possibility of the same clones being selected for both places. Mean heritability between clones (0.724), coefficient of individual genetic variation (10.9%) and relative variation (0.916), showed the possibility of obtaining gains by selecting clones with higher growth, which was estimated in 3.1% for both sites together. A total of 15,196 markers SNPs were used in the genomic selection for the DBH, but after cleaning of SNPs data, the number was reduced for 15,196 (23.5%). The predictive capacity was expected to be low or negative (-0.15) for this population given the population size (78 individuals). We used the model rrBLUP with a validation of Jackknife. The model do not showed precision to predict the DBH. These results were consistent with theoretical expectations, which indicate that it is necessary to have an improvement population of at least 1,000 phenotyped and genotyped individuals. The DBH is the most important trait in the breeding of the genus Eucalyptus. However its quantitative nature added to the time necessary for this phenotype to develop makes the early detection of this trait are difficult. The identification of molecular markers associated with quantitative phenotypes is a good choice for the identification of QTLs that will help the early detection of individuals with high DBH. Significant markers associated to DBH , were indentificated into the chromosome 6, suggesting the presence of a QTL in this chromosome. Since they are clones originated from vegetative propagation and a full-sibs single-progeny, they should preferably be used for reforestation based on their cloning, since mating between clones can generate endogamy by biparental inbreeding. The utilization of SNPs helped to confirm the degree of parentage between the clones as well as clonal identity control.
Detecção de QTL associado a DAP em Eucaliptus grandis x Eucaliptus Globulus monoprogênie
Keywords: Eucalyptus breeding; Quantitative genetics; Genomic Wide Prediction (GWP); Genomic Wide Association (GWAS); SNPs Markers; Uruguay